Effects of Hydrogen on Endurance Characteristics in NAND Flash Memories. (1st December 2022) - Chiu, Yung-Yueh; Liu, Wen-Chien; Chen, Yu-Jung; Kumaria, Roshni; Takeshita, Toshiaki; Yano, Masaru; Shirota, Riichiro
Abstract : This study comprehensively investigates the effect of hydrogen content in forming gas annealing (FGA) on the endurance of NAND flash memories by statistically analyzing the transconductance ( G m, m a x ) characteristics. The G m, m a x degradation ( Δ G m, m a x ) worsened with higher cycling temperature, delayed time period from erasing to programming ( t E P ) operation, and higher word-line bias ( V A ) during t E P . Moreover, these effects become more pronounced as the hydrogen content in FGA increases. Using the measured G m, m a x distributions and Monte -Carlo TCAD technology, the activation energy ( E A ) of oxide damage creation can be extracted. The extracted E A values were 50 meV and 160 meV for the diluted (4%) and pure (100%) hydrogen samples, respectively. This suggests that a higher hydrogen concentration results in more ionized hydrogen atoms remaining in the oxide layer. During t E P, these hydrogen ions can drift near the Si/SiO2 surface, where they may react to form trap states. E A is revealed to have a linear relationship with respect to V A, where the slope is independent of the hydrogen content in FGA.